2023
DOI: 10.1136/bmj-2022-071726
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment after cancer treatment: mechanisms, clinical characterization, and management

Abstract: Cognitive impairment is a debilitating side effect experienced by patients with cancer treated with systemically administered anticancer therapies. With around 19.3 million new cases of cancer worldwide in 2020 and the five year survival rate growing from 50% in 1970 to 67% in 2013, an urgent need exists to understand enduring side effects with severe implications for quality of life. Whereas cognitive impairment associated with chemotherapy is recognized in patients with breast cancer, researchers have starte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 193 publications
0
35
0
Order By: Relevance
“…[40][41][42] However, it is unclear to what extent these heterogenous neuropsychiatric symptoms are attributable to CAR-T cell therapy versus the pre-existing burden of toxicities, mental health disorders, and cognitive difficulties associated with the underlying disease, comorbidities, and prior cancer treatment. 43 Reassuringly, recent studies incorporating longitudinal neuropsychological testing have concluded that most CAR-T cell recipients recover with no permanent neurocognitive deficits or with similar or only slight deterioration in neurocognitive performance compared to baseline. 39,44,45 Nevertheless, continued decline in perceived cognitive functioning has been reported by up to 25% of patients, particularly among those with severe ICANS or higher levels of baseline fatigue, anxiety, and depression.…”
Section: Late-onset or Persistent Neurotoxicitymentioning
confidence: 99%
See 3 more Smart Citations
“…[40][41][42] However, it is unclear to what extent these heterogenous neuropsychiatric symptoms are attributable to CAR-T cell therapy versus the pre-existing burden of toxicities, mental health disorders, and cognitive difficulties associated with the underlying disease, comorbidities, and prior cancer treatment. 43 Reassuringly, recent studies incorporating longitudinal neuropsychological testing have concluded that most CAR-T cell recipients recover with no permanent neurocognitive deficits or with similar or only slight deterioration in neurocognitive performance compared to baseline. 39,44,45 Nevertheless, continued decline in perceived cognitive functioning has been reported by up to 25% of patients, particularly among those with severe ICANS or higher levels of baseline fatigue, anxiety, and depression.…”
Section: Late-onset or Persistent Neurotoxicitymentioning
confidence: 99%
“…Nevertheless, continued decline in perceived cognitive functioning has been reported by up to 25% of patients, particularly among those with severe ICANS or higher levels of baseline fatigue, anxiety, and depression 42 . Long‐term survivors of CAR‐T cell therapy may thus benefit from continued monitoring and support of neurocognitive health as they re‐integrate into their family and societal roles, including measures to promote physical activity, nutrition, sleep, and cognitive exercise 43 …”
Section: Late‐onset or Persistent Neurotoxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…174 Traditional cancer therapies, including chemotherapies and radiation, have long-lasting lethal impacts on nervous system activities, evident as cancer therapy-associated cognitive disruption (impaired memory, attention, multitasking, and sometimes enhanced anxiety) and as peripheral neuropathies (motor weakness, sensory loss, or pain). 174 Similar prolonged nervous system impact by novel targeted and cancer immune therapies require attention. Cancer therapies differentially influence cognition and the nerve types impacted in chemotherapy-induced peripheral neuropathy.…”
Section: Cancer Therapies' Iinfluence On the Nervous Systemmentioning
confidence: 99%